Dynamics of collective motion across time and species. (10th April 2023) - Papadopoulou, Marina; Fürtbauer, Ines; O'Bryan, Lisa R.; Garnier, Simon; Georgopoulou, Dimitra G.; Bracken, Anna M.; Christensen, Charlotte; King, Andrew J.
Abstract : Most studies of collective animal behaviour rely on short-term observations, and comparisons of collective behaviour across different species and contexts are rare. We therefore have a limited understanding of intra- and interspecific variation in collective behaviour over time, which is crucial if we are to understand the ecological and evolutionary processes that shape collective behaviour. Here, we study the collective motion of four species: shoals of stickleback fish ( Gasterosteus aculeatus ), flocks of homing pigeons ( Columba livia ), a herd of goats ( Capra aegagrus hircus ) and a troop of chacma baboons ( Papio ursinus ). First, we describe how local patterns (inter-neighbour distances and positions), and group patterns (group shape, speed and polarization) during collective motion differ across each system. Based on these, we place data from each species within a 'swarm space', affording comparisons and generating predictions about the collective motion across species and contexts. We encourage researchers to add their own data to update the 'swarm space' for future comparative work. Second, we investigate intraspecific variation in collective motion over time and provide guidance for researchers on when observations made over different time scales can result in confident inferences regarding species collective motion. This article is part of a discussion meeting issue 'Collective behaviour through time'.